Impact of a high dietary fiber cereal meal intervention on the progression of liver fibrosis in T2DM with MASLD - Chen, Xi-Shuang; Liu, Hui-Zhen; Huang, Fang; Meng, Jian; Fang, Jing-Xian; Han, Yu; Zou, Hui-Ming; Gu, Qing; Hu, Xue; Ma, Qian-Wen; Han, Yue-Xia; Wang, Sui-Jun (Frontiers in Endocrinology, 2025)
AimsThis study aimed to investigate the ameliorative effect of dietary fiber on hepatic fibrosis in T2DM combined with MASLD and to seek the appropriate dose of DF for this population.Material and methodsThis study was a randomized, controlled, open clinical trial. Patients with T2DM and MASLD were recruited from January 2024 to March 2024 in our hospital using the Interactive Web Response System (IWRS) in a 1:1:1 ratio randomly divided into 3 groups. The control patients received traditional diabetes education. Based on health education, the intervention group took DF supplements (Shanghai Jiuben Technology Co., Ltd.) daily for 12 weeks. Each packet of the supplement is 50 grams and contains approximately 12 grams of dietary fiber (DF). The intervention group was randomly assigned to two different groups. One group received 24 grams of fiber, which was obtained by consuming two packets, each containing 12 grams of fiber. The other group received 12 grams of fiber by consuming one packet.ResultsBoth interventions showed a more significant decrease in HbA1c levels than the control group, but only the difference between the control and 24g intervention groups was statistically significant(-0.6 ± 0.5 vs -1.6 ± 0.6, P<.001). The 24g intervention group showed a substantial decrease in FPG compared to the control group and the 12g intervention both at week 8 and week 12 (p < 0.05). Both intervention groups experienced significant reductions in FIB-4 levels (p<0.05), with the intervention with 24g group showing the most significant decrease.ConclusionOur study demonstrated that dietary fiber improved liver fibrosis and glycemic control, with a more pronounced effect in patients from the 24g Intervention group. However, this group had no statistically significant change in BMI, possibly due to higher caloric intake from additional fiber.